The Influence of Altitude Toward Vegetative and Generative Growth of Sugar Palm (Arenga pinnata) - Akbar, Difa Adiba; Yuniastuti, Endang; Supriyono, Supriyono (Agro Bali : Agricultural Journal, 2025)
Sugar palm is a member of the palm family that offers many benefits. Palm sugar is produced from the male flower, while the fruit is produced from the female flower. The potential of this resource has not been fully realized because most of it is sourced from the wild. This research aims to determine the differences in the growth of palms based on altitude. The research was conducted from October 2023 to March 2024 in Sleman, Kulon Progo, and Purworejo regions. Treatment of altitude is divided into three, namely lowlands (0-400 masl), medium (401-700 masl), and highlands (>700 masl). The parameters used in this research were plant height, stem, number of leaves, leaf width and length, number of productive and unproductive leaves, number of bunches, number of female and male flowers, and number and weight of fruits. Data on vegetative growth were analyzed using ANOVA, and then LSD for further and data on generative growth used the Kruskal Wallis test with a significance level of 95%. The result showed a significant difference between vegetative growth and altitude except for the number of productive leaves and generative growth; there was only a significant difference in the number of male flowers.